A Characterization of Projective Special Unitary Group U3(7) by nse. (22nd August 2013) - Liu, Shitian
Abstract : Let G a group and ω ( G ) be the set of element orders of G . Let k ∈ ω ( G ) and let s k be the number of elements of order k in G . Let nse( G ) = { s k ∣ k ∈ ω ( G ) } . In Khatami et al. and Liu's works, L 3 ( 2 ) and L 3 ( 4 ) are uniquely determined by nse( G ) . In this paper, we prove that if G is a group such that nse( G ) = nse( U 3 ( 7 ) ), then G ≅ U 3 ( 7 ) .